Pharmaceutical inspection in ten decentralized bases of the urgency mobile care service (SAMU) in southwest Paraná - Francieli Molinett (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
The ascension of clinical pharmacy services enables this practitioner to carry out actions directed to the patient, promoting the rational use of medications and improving the quality of life. These actions can be performed through pharmaceutical consultations in order to optimize the patient's pharmacotherapy and to monitor periodically their health conditions to evaluate the efficacy of the treatment. Objectives: to evaluate the impact of the clinical pharmacy service in polypharmacy patients attended at a large hospital outpatient clinic. Methods: data were collected from the consultations carried out for six months at the Pharmaceutical Care Outpatient Clinic and these data were analyzed statistically. Results: there was a significant increase in morbidity control between the first and second visits, from 2,52 (± 1,465), on average, to 2,95 (± 1,519), p=0.003, indicating the potential benefit of pharmaceutical care on patient's health. There was also a persistence in the number of complaints and in the number of interventions performed, reiterating the need for continuous follow-up to solve all patient problems. Conclusion: outpatient follow-up by a clinical pharmacist has a potential for obtaining positive outcomes in the patient's health.